Environmental Conditions, Phytochemical Constituents, and Antibacterial Activities of Two Philippine Medicinal Vitaceae Species - Jeff Miranda Opena; Rachel Sotto (Journal of Tropical Life Science, 2022)
Plants are utilized for medicinal, therapeutic, nutritional, and industrial importance. This study investigated the phytochemical constituents and antibacterial activities of two medicinal Vitaceae species, namely: Cayratia trifolia and Tetrastigma harmandii. The growing environment (location, elevation, soil properties, and associated plants) of the species in northeastern Cagayan, Luzon, Philippines, were assessed and leaf samples were collected for phytochemical screening and antibacterial analysis. T. harmandii dominated the population found growing in various habitats such as hills, residential areas, near coastal areas and island shorelines, nipa plantations, agricultural and grasslands, near bodies of water, caves, and secondary growth forests while C. trifolia were only found growing in swamps, hills, and secondary growth forests. Both plants were found climbing in plant species like ipil-ipil (Leucaena leucocephala)and kakawate (Gliciridia sepium). T. harmandii populations were growing in soils with lower soil pH and higher nutrient content as compared to C. trifolia populations which grew in soils with higher pH and lower nutrients. Antioxidant properties were exhibited by the presence of secondary metabolites. Alkaloids, flavonoids, phenols, terpenoids, anthocyanins, tannins, and saponins were detected in C. trifolia ethanolic leaf extracts while phenols, terpenoids, tannins, and saponins were detected in T. harmandii. Both species showed inhibitory activity against Staphylococcus aureus. In addition, a slight activity against Klebsiella aerogenes was observed for T. harmandii. Thus, C. trifolia and T. harmandii also have antibacterial properties.